High-toughness wave-absorbing composite material as well as preparation method and application thereof
By introducing TiC and CrB2 into B4C and preparing composite materials with (TixCr1-x) B2-graphite nested structure by using reactive hot press sintering technology, the problem of insufficient mechanical properties and electromagnetic wave absorption performance of B4C materials in the prior art is solved, and the wide application of high-strength and tough wave-absorbing composite materials is achieved.
Patent Information
- Application Number
- CN202510093395.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The prior art is difficult to improve the mechanical properties of boron carbide (B4C) while improving its electromagnetic wave absorption performance, which limits its wide application in integrated protection and stealth applications.
B4C, TiC and CrB2 powders were used as raw materials, and B4C-(TixCr1-x)B2-graphite composite materials with (TixCr1-x)B2-graphite nested structure was prepared by reacting hot press sintering process, and the ratio of TiC and CrB2 was adjusted to improve the mechanical properties and electromagnetic wave absorption properties of the material.
The bending strength, fracture toughness and electromagnetic wave absorption performance of B4C-(TixCr1-x)B2-graphite composite material have been significantly improved, achieving the effect of wide-band strong absorption, meeting the new requirements of modern warfare for armor materials.
Smart Images

Figure CN119912262A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of novel bulletproof armor manufacturing, and in particular to a high-strength and tough wave-absorbing composite material and a preparation method and application thereof. Background Art
[0002] In recent years, the rapid development of military radar technology has put forward higher requirements for traditional bulletproof armor. Traditional stealth technology usually coats the outside of the armor with an absorbing coating. However, this method has many problems, such as increased equipment weight, poor broadband stealth performance, and high regular maintenance costs, which can no longer meet the needs of modern battlefields. Therefore, through structural design, the armor material is given excellent absorbing properties while meeting the mechanical performance requirements, and the integration of protection and stealth is achieved, which is expected to improve the above problems.
[0003] Boron carbide (B4C) has high hardness (>35GPa), low density (2.52g·cm -3 ), high elastic modulus, etc., and is a very promising armor material. At the same time, as a semiconductor material, B4C has certain electromagnetic wave absorption properties. Therefore, B4C is expected to become a new bulletproof material that integrates stealth protection. However, the low diffusion coefficient and strong covalent bond of B4C make it difficult to densify, and the material has poor fracture toughness (K IC <2.20MPa·m 1 / 2 ), and the electromagnetic wave loss mechanism of B4C is single and the impedance matching is poor, which limits its wide application.
[0004] At present, the introduction of second phases such as carbides, borides, and graphene is the main method to improve the mechanical properties of B4C ceramics. For example, B4C-HfB2 composites and B4C-W2B5 composites, due to the residual stress generated by the mismatch of thermal expansion coefficients between B4C and the second phase during high-temperature cooling, can effectively increase the crack deflection and crack bridging of the material during the fracture process, thereby improving its fracture toughness. However, there are relatively few studies on the electromagnetic wave absorption performance of B4C in the prior art.
[0005] Therefore, how to improve the mechanical properties of B4C while improving its electromagnetic wave absorption performance and realize the integrated stealth protection of B4C composite materials is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a high-strength and toughness radar-absorbing composite material and a preparation method and application thereof, so as to meet the new requirements of modern warfare for armor materials.
[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0008] A high-strength and tough wave-absorbing composite material, the high-strength and tough wave-absorbing composite material is B4C-(Ti x Cr 1-x )B2-graphite; B4C-(Ti x Cr 1-x )B2-graphite, (Ti x Cr 1-x )The content of B2 is 20 vol.% (volume percentage), and 0.48≤x≤0.89.
[0009] The present invention also provides a method for preparing a high-strength and tough wave-absorbing composite material, comprising the following steps:
[0010] S1, weigh the raw materials according to the following mass percentages: 69.54-72.35wt.% (mass percentage) of B4C, 13.11-24.11wt.% of TiC, and 3.54-17.35wt.% of CrB2; mix the raw materials uniformly to obtain a mixed powder;
[0011] S2, placing the mixed powder in a mold for hot pressing sintering, the sintering temperature of the hot pressing sintering is 1800-2000°C, the sintering pressure of the hot pressing sintering is 20-60MPa, and the mixture is kept at the sintering temperature for 1-3h; after the sintering is completed, the mixture is cooled to obtain a high-strength and tough absorbing composite material B4C-(Ti x Cr 1-x )B2-graphite (can be referred to as B4C-(Ti x Cr 1-x )B2-graphite composite material).
[0012] Preferably, in step S1, the purity of B4C is 99.9% and the particle size is 0.5 μm; the purity of TiC is 99.5% and the particle size is 1-2 μm; the purity of CrB2 is 99.5% and the particle size is 1-2 μm.
[0013] Preferably, in step S1, the mixing process of the raw materials is: adding the raw materials to anhydrous ethanol and then ball milling to obtain a suspension; and rotary evaporating the suspension and grinding and sieving to obtain a mixed powder.
[0014] Preferably, in step S1, the mass ratio of anhydrous ethanol to raw material is (1-2):1, the mass ratio of ball to material in the ball milling process is (1-3):1, the ball milling speed is 60-120 r / min, and the ball milling time is 12-24 h.
[0015] Further preferably, in step S1, the mass ratio of anhydrous ethanol to raw material is 1.4:1, the mass ratio of balls to materials in the ball milling process is 2:1, the ball milling speed is 90 r / min, and the ball milling time is 12 h.
[0016] Preferably, in the step S1, a polytetrafluoroethylene ball milling jar is used in the ball milling process, and zirconium oxide ball milling balls are used as ball milling media.
[0017] Specifically, a drum ball mill is used for ball milling.
[0018] Preferably, in step S1, the suspension is dried by rotary evaporation at 40-55°C for 0.5-2h; and a 200-mesh sieve is used during sieving.
[0019] Further preferably, in step S1, the suspension is dried by rotary evaporation at 50°C for 0.5h.
[0020] Preferably, in step S2, the heating rate of hot pressing sintering is: when the temperature is increased from room temperature to 1000°C, the heating rate is 10°C / min; when the temperature is increased from 1000°C to 1600°C, the heating rate is 8°C / min; when the temperature is increased from 1600°C to the sintering temperature, the heating rate is 5°C / min.
[0021] Further preferably, in step S2, the sintering temperature of hot pressing sintering is 1900° C., the sintering pressure is 60 MPa, and the holding time is 1 hour.
[0022] Preferably, in step S2, the mold is a graphite mold; and the sintering environment is a vacuum environment or an inert atmosphere.
[0023] The present invention also includes the use of the high-strength and toughness absorbing composite material or the high-strength and toughness absorbing composite material prepared by the above preparation method in bullet-proof materials.
[0024] Working principle:
[0025] (1) The present invention uses B4C powder, TiC powder, and CrB2 powder as raw materials, and utilizes reaction hot pressing sintering to prepare (Ti x Cr 1-x )B4C-(Ti x Cr 1-x )B2-graphite composite material can effectively improve B4C-(Ti x Cr 1-x )B2-graphite composite material has good mechanical properties and electromagnetic wave absorption performance. These effects are mainly due to the addition ratio of TiC and CrB2 in the raw materials and the process of reaction hot pressing sintering. When TiC and CrB2 are added to B4C, a reaction occurs during the sintering process to generate (Ti x Cr 1-x )B2 and graphite, (Ti x Cr 1-x)B2 and graphite form a nested structure.
[0026] First, TiC and CrB2 were introduced to form (Ti x Cr 1-x )B2 solid solution, by adjusting the ratio of TiC and CrB2 to form (Ti x Cr 1-x )B2 solid solution, on the one hand (Ti x Cr 1-x )B2 lattice distortion can increase the internal stress of the material, hinder dislocation movement, and achieve solid solution strengthening, thereby regulating the B4C-(Ti x Cr 1-x )B2-graphite composite mechanical properties, on the other hand (Ti x Cr 1-x The large number of defects formed by B2 enhance the dipole polarization, which can absorb electromagnetic waves more effectively, thereby broadening the effective absorption bandwidth.
[0027] Secondly, graphite and (Ti x Cr 1-x )B2 forms a nested structure with B4C. Graphite has good energy absorption capacity. When the crack expands to the nested structure, it can absorb and dissipate part of the crack extension energy, thereby improving the B4C-(Ti x Cr 1-x )B2-graphite composite material has better toughness, and more interfaces are formed. The interface polarization increases, which increases the effective absorption bandwidth of the material and achieves broadband strong absorption of electromagnetic waves. x Cr 1-x ) The flexural strength of B2-graphite composite materials is 415.54-575.94MPa and the fracture toughness is 4.98-6.17MPa·m 1 / 2 When the fitting thickness is 1.2 mm, the reflection loss value reaches -43.59 dB, and the effective absorption bandwidth is as high as 3.60 GHz. x Cr 1-x )B2-graphite has both excellent mechanical properties and electromagnetic wave absorption properties.
[0028] (2) The B4C-(Ti x Cr 1-x )B2-graphite composite material has the advantages of high fracture toughness, high bending strength and strong wave absorption performance, and has good repeatability, simple steps and is easy to implement.
[0029] Beneficial effects:
[0030] The present invention adopts B4C powder, TiC powder and CrB2 powder as raw materials, and utilizes reaction hot pressing sintering to prepare (Ti x Cr 1-x )B4C-(Ti x Cr 1-x )B2-graphite composite material can effectively improve B4C-(Ti x Cr 1-x )B2-graphite composite material mechanical properties and electromagnetic wave absorption performance. The B4C-(Ti x Cr 1-x )B2-graphite composite material has the advantages of high fracture toughness, high bending strength and strong wave absorption performance, and has good repeatability, simple steps and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )XRD pattern of B2-graphite;
[0032] Figure 2 The high-strength and tough wave-absorbing composite material B4C-(Ti 0.58 Cr 0.42 ) SEM image of B2-graphite fracture;
[0033] Figure 3 The high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )B2-graphite fracture toughness and bending strength data;
[0034] Figure 4 The high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )Reflection loss curve of the best matching thickness of B2-graphite. DETAILED DESCRIPTION
[0035] The present invention is further described in detail with reference to specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses industrial purity or conventional purity used in the art.
[0037] The devices used in the present invention are not particularly limited and can be any of the commonly used devices in the art.
[0038] In the following examples, B4C powder, TiC powder and CrB2 powder are all commercially available products. The volume percentage is calculated based on the theoretical volume obtained by converting the mass to the theoretical density value.
[0039] The B4C powder used in the following embodiments was purchased from Zhengzhou Songshan Boron Technology Co., Ltd., with an average particle size of 0.5 μm and a purity of 99.9%; the TiC powder used was purchased from Beijing Huawei Ruike Chemical Co., Ltd., with a particle size of 1-2 μm and a purity of 99.5%; the CrB2 powder used was purchased from Shanghai Titan Technology Co., Ltd., with a particle size of 1-2 μm and a purity of 99.5%.
[0040] Example 1
[0041] A method for preparing a high-strength and tough wave-absorbing composite material comprises the following steps:
[0042] (1) Weigh 72.35wt.% B4C powder, 24.11wt.% TiC powder, and 3.54wt.% CrB2 powder as raw materials, place the powders in a polytetrafluoroethylene ball mill in turn, add anhydrous ethanol, and use zirconium oxide ball milling balls as ball milling media for roller milling until the slurry is milled into a uniform suspension. The mass ratio of anhydrous ethanol to raw materials is 1:1, and the mass ratio of balls to materials is 1:1; the ball milling speed is 90r / min, and the ball milling time is 12h. After the ball milling is completed, the suspension is separated from the zirconium oxide ball milling balls, and then the suspension is dried using a rotary evaporator, the drying time is 0.5h, and the drying temperature is 40℃; the dried mixed powder is sieved through a 200-mesh sieve and set aside.
[0043] (2) The mixed powder is placed in a graphite mold and sintered in a hot press sintering furnace. The temperature is raised from room temperature to 1000°C at 10°C / min, then to 1600°C at 8°C / min, and then to 1900°C at 5°C / min for 1 hour. The pressure is 60 MPa. After sintering, the furnace is cooled, the mold is taken out, and the sintered body is separated from the mold to obtain a high-strength and tough wave-absorbing composite material B4C-(Ti 0.89 Cr 0.11 )B2-graphite, denoted as T 0.89 C 0.11 .
[0044] After testing, the high-strength and tough wave-absorbing composite material T prepared in this embodiment 0.89 C 0.11The bending strength is 524MPa and the fracture toughness is 4.98MPa·m 1 / 2 The minimum reflection loss in the frequency range of 2-18GHz is -32.02dB (8.08GHz, 3.2mm), and the effective absorption bandwidth is 2.88GHz (3.2mm).
[0045] Example 2
[0046] A method for preparing a high-strength and tough wave-absorbing composite material comprises the following steps:
[0047] (1) Weigh 71.64wt.% B4C powder, 21.31wt.% TiC powder, and 7.05wt.% CrB2 powder as raw materials, place the powders in a polytetrafluoroethylene ball mill in turn, add anhydrous ethanol, and use zirconium oxide ball milling balls as ball milling media for roller milling until the slurry is ball milled into a uniform suspension. The mass ratio of anhydrous ethanol to raw materials is 2:1, and the mass ratio of balls to materials is 3:1; the ball milling speed is 120r / min, and the ball milling time is 24h. After the ball milling is completed, the suspension is separated from the zirconium oxide ball milling balls, and then the suspension is dried using a rotary evaporator for 1.5h at a drying temperature of 55°C; the dried mixed powder is sieved through a 200-mesh sieve for later use.
[0048] (2) Place the mixed powder in a graphite mold and sinter it in a hot press sintering furnace. Raise the temperature from room temperature to 1000°C at 10°C / min, then to 1600°C at 8°C / min, and then to 1900°C at 5°C / min for 1 hour, with a pressure of 60 MPa. After sintering, cool it in the furnace, take out the mold, separate the sintered body from the mold, and obtain a high-strength and tough wave-absorbing composite material B4C-(Ti 0.79 Cr 0.21 )B2-graphite, denoted as T 0.79 C 0.21 .
[0049] After testing, the high-strength and tough wave-absorbing composite material T prepared in this embodiment 0.79 C 0.21 The bending strength is 575MPa and the fracture toughness is 6.17MPa·m 1 / 2 The minimum reflection loss in the frequency range of 2-18GHz is -33.26dB (8.64GHz, 3.0mm), and the effective absorption bandwidth is 4.80GHz (3.0mm).
[0050] Example 3
[0051] A method for preparing a high-strength and tough wave-absorbing composite material comprises the following steps:
[0052] (1) Weigh 70.93wt.% B4C powder, 18.55wt.% TiC powder, and 10.52wt.% CrB2 powder as raw materials, place the powders in a polytetrafluoroethylene ball mill in turn, add anhydrous ethanol, and use zirconium oxide ball milling balls as ball milling media for roller milling until the slurry is milled into a uniform suspension. The mass ratio of anhydrous ethanol to raw materials is 1.3:1, and the mass ratio of balls to materials is 1.5:1; the ball milling speed is 95r / min, and the ball milling time is 15h. After the ball milling is completed, the suspension is separated from the zirconium oxide ball milling balls, and then the suspension is dried using a rotary evaporator for 1h at a drying temperature of 45°C; the dried mixed powder is sieved through a 200-mesh sieve for later use.
[0053] (2) Place the mixed powder in a graphite mold and sinter it in a hot press sintering furnace. Raise the temperature from room temperature to 1000°C at 10°C / min, then to 1600°C at 8°C / min, and then to 1850°C at 5°C / min and keep it for 1 hour at a pressure of 60 MPa. After sintering, cool it in the furnace, take out the mold, separate the sintered body from the mold, and obtain a high-strength and tough wave-absorbing composite material B4C-(Ti 0.68 Cr 0.32 )B2-graphite, denoted as T 0.68 C 0.32 .
[0054] After testing, the high-strength and tough wave-absorbing composite material T prepared in this embodiment 0.68 C 0.32 The bending strength is 518MPa and the fracture toughness is 5.38MPa·m 1 / 2 The minimum reflection loss in the frequency range of 2-18GHz is -29.56dB (9.04GHz, 2.8mm), and the effective absorption bandwidth is 5.84GHz (2.8mm).
[0055] Example 4
[0056] A method for preparing a high-strength and tough wave-absorbing composite material comprises the following steps:
[0057] (1) Weigh 70.23wt.% B4C powder, 15.82wt.% TiC powder, and 13.95wt.% CrB2 powder as raw materials, place the powders in a polytetrafluoroethylene ball mill in turn, add anhydrous ethanol, and use zirconium oxide ball milling balls as ball milling media for roller milling until the slurry is ball milled into a uniform suspension. The mass ratio of anhydrous ethanol to raw materials is 1.8:1, and the mass ratio of balls to materials is 2.5:1; the ball milling speed is 105r / min, and the ball milling time is 21h. After the ball milling is completed, the suspension is separated from the zirconium oxide ball milling balls, and then the suspension is dried using a rotary evaporator for 0.5h at a drying temperature of 50°C; the dried mixed powder is sieved through a 200-mesh sieve for later use;
[0058] (2) Place the mixed powder in a graphite mold and sinter it in a hot press sintering furnace. Raise the temperature from room temperature to 1000°C at 10°C / min, then to 1600°C at 8°C / min, then to 1900°C at 5°C / min and keep it for 2 hours at a pressure of 60 MPa. After sintering, cool it in the furnace, take out the mold, separate the sintered body from the mold, and obtain the high-strength and toughness absorbing composite material B4C-(Ti 0.58 Cr 0.42 )B2-graphite, denoted as T 0.58 C 0.42 .
[0059] After testing, the high-strength and tough wave-absorbing composite material T prepared in this embodiment 0.58 C 0.42 The bending strength is 458.14MPa and the fracture toughness is 5.19MPa·m 1 / 2 The minimum reflection loss in the frequency range of 2-18GHz is -42.59dB (9.20GHz, 2.5mm), and the effective absorption bandwidth is 6.56GHz (2.6mm).
[0060] Example 5
[0061] A method for preparing a high-strength and tough wave-absorbing composite material comprises the following steps:
[0062] (1) Weigh 69.54wt.% B4C powder, 13.11wt.% TiC powder, and 17.35wt.% CrB2 powder as raw materials, place the powders in a polytetrafluoroethylene ball mill in turn, add anhydrous ethanol, and use zirconium oxide ball milling balls as ball milling media for roller milling until the slurry is ball milled into a uniform suspension. The mass ratio of anhydrous ethanol to raw materials is 1.5:1, and the mass ratio of balls to materials is 2:1; the ball milling speed is 100r / min, and the ball milling time is 18h. After the ball milling is completed, the suspension is separated from the zirconium oxide ball milling balls, and then the suspension is dried using a rotary evaporator for 1h at a drying temperature of 55°C; the dried mixed powder is sieved through a 200-mesh sieve for later use;
[0063] (2) Place the mixed powder in a graphite mold and sinter it in a hot press sintering furnace. Raise the temperature from room temperature to 1000°C at 10°C / min, then to 1600°C at 8°C / min, then to 1900°C at 5°C / min and keep it for 1 hour at a pressure of 60 MPa. After sintering, cool it in the furnace, take out the mold, separate the sintered body from the mold, and obtain a high-strength and tough wave-absorbing composite material B4C-(Ti 0.48 Cr 0.52 )B2-graphite, denoted as T 0.48 C 0.52 .
[0064] After testing, the high-strength and tough wave-absorbing composite material T prepared in this embodiment 0.48 C 0.52 The bending strength is 415MPa and the fracture toughness is 5.02MPa·m 1 / 2 The minimum reflection loss in the frequency range of 2-18GHz is -28.84dB (9.44GHz, 2.6mm), and the effective absorption bandwidth is 7.36GHz (2.7mm).
[0065] The high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )B2-graphite was subjected to XRD test, and the results were as follows Figure 1 As shown in the figure, the components of the high-strength and tough wave-absorbing composite material prepared by this method are B4C, (Ti x Cr 1-x )B2, graphite.
[0066] The high-strength and tough wave-absorbing composite material T prepared in Example 4 0.58 C 0.42 The fracture surface was subjected to SEM test, and the test results were as follows: Figure 2 As shown, the results show that the generated (Ti 0.58 Cr 0.42)B2 and graphite form a nested structure. x Cr 1-x )B2 can improve B4C-(Ti x Cr 1-x )B2-graphite composite material flexural strength, graphite can absorb and dissipate part of the crack propagation energy to improve the B4C-(Ti x Cr 1-x )Toughness of B2-graphite composites.
[0067] The high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )B2-graphite's fracture toughness and bending strength were tested. The test results are as follows Figure 3 As shown in the figure, it is known that by adjusting the addition ratio of TiC and CrB2, it can be seen that the introduction of a certain amount of Cr can improve the high-strength and toughness absorbing composite material B4C-(Ti x Cr 1-x )Fracture toughness and flexural strength of B2-graphite.
[0068] The high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )B2-graphite was used to test the electromagnetic wave absorption performance and draw Figure 4 The reflection loss curves of the best matching thickness of Examples 1-5 are shown. It can be seen that the high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )B2-graphite has certain electromagnetic wave absorption performance. By adjusting the addition ratio of TiC and CrB2, it can be seen that with the increase of Cr content, the effective absorption bandwidth with reflection loss below -10dB gradually increases. x Cr 1-x )B2 forms a large number of defects that enhance the dipole polarization, and (Ti x Cr 1-x )B2-graphite nested structures form more interfaces ( Figure 2 ), enhancing the interface polarization, can more effectively absorb electromagnetic waves, proving that regulating the addition ratio of TiC and CrB2 can increase the B4C-(Ti x Cr 1-x )B2-graphite composite material has an effective absorption bandwidth, which greatly improves the B4C-(Ti x Cr 1-x )Electromagnetic wave absorption properties of B2-graphite composite materials.
[0069] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A high-strength and tough wave-absorbing composite material, characterized in that: High strength and toughness absorbing composite material is B4C-(Ti x Cr 1-x )B2-graphite; B4C-(Ti x Cr 1-x )B2-graphite, (Ti x Cr 1-x )The content of B2 is 20 vol.%, and 0.48≤x≤0.
89.
2. A method for preparing the high-strength and tough wave-absorbing composite material according to claim 1, characterized in that: The following steps are involved: S1, weigh the raw materials according to the following mass percentages: 69.54-72.35wt.% B4C, 13.11-24.11wt.% TiC, and 3.54-17.35wt.% CrB2; mix the raw materials evenly to obtain a mixed powder; S2, placing the mixed powder in a mold for hot pressing sintering, the sintering temperature of the hot pressing sintering is 1800-2000°C, the sintering pressure of the hot pressing sintering is 20-60MPa, and the sintering temperature is kept at sintering temperature for 1-3h; After sintering, the high-strength and tough wave-absorbing composite material B4C-(Ti x Cr 1-x )B2-graphite.
3. The method for preparing a high-strength and tough wave-absorbing composite material according to claim 2, characterized in that: In the step S1, the purity of B4C is 99.9% and the particle size is 0.5 μm; the purity of TiC is 99.5% and the particle size is 1-2 μm; the purity of CrB2 is 99.5% and the particle size is 1-2 μm.
4. The method for preparing a high-strength and tough wave-absorbing composite material according to claim 2, characterized in that: In step S1, the raw material mixing process is: adding the raw material to anhydrous ethanol and then ball milling to obtain a suspension; rotary evaporating the suspension and grinding and sieving to obtain a mixed powder.
5. The method for preparing a high-strength and tough wave-absorbing composite material according to claim 4, characterized in that: In the step S1, the mass ratio of anhydrous ethanol to raw material is (1-2):1, the mass ratio of ball to material in the ball milling process is (1-3):1, the ball milling speed is 60-120 r / min, and the ball milling time is 12-24 h.
6. The method for preparing a high-strength and tough wave-absorbing composite material according to claim 4, characterized in that: In the step S1, a polytetrafluoroethylene ball milling jar is used in the ball milling process, and zirconium oxide ball milling balls are used as ball milling media.
7. The method for preparing a high-strength and tough wave-absorbing composite material according to claim 4, characterized in that: In the step S1, the suspension is dried by rotary evaporation at 40-55°C for 0.5-2h; and a 200-mesh screen is used during the sieving process.
8. The method for preparing a high-strength and tough wave-absorbing composite material according to claim 2, characterized in that: In step S2, the heating rate of hot pressing sintering is: when the temperature is raised from room temperature to 1000°C, the heating rate is 10°C / min; when the temperature is raised from 1000°C to 1600°C, the heating rate is 8°C / min; when the temperature is raised from 1600°C to the sintering temperature, the heating rate is 5°C / min.
9. The method for preparing a high-strength and tough wave-absorbing composite material according to claim 2, characterized in that: In step S2, the mold is a graphite mold; and the sintering environment is a vacuum environment or an inert atmosphere.
10. Use of the high-strength and tough wave-absorbing composite material as claimed in claim 1 or the high-strength and tough wave-absorbing composite material prepared by the preparation method according to any one of claims 2 to 9 in bulletproof materials.
Citation Information
Patent Citations
Preparation method and application of boron carbide composite material
CN111960850A
High-performance composite ceramic based on large-particle-size SiC powder and rapid preparation method
CN117720350A
SU367989A1